Active BR signalling adjusts the subcellular localisation of BES1/HSP90 complex formation. (27th September 2019) - Samakovli, D.; Roka, L.; Plitsi, P.‐K.; Kaltsa, I.; Daras, G.; Milioni, D.; Hatzopoulos, P.
Abstract: Heat shock proteins 90 (HSP90) are essential and play critical roles in the adaptation of organisms to diverse stimuli. In plants, HSP90 are involved in auxin, jasmonate and brassinosteroid (BR) signalling pathways. The BR‐promoted activation of the BES1 transcription factor regulates BR‐responsive genes. Using genetic, physiological, fluorescence live cell imaging, molecular and biochemical approaches, such as phenotypic analysis, co‐immunoprecipitation assay, yeast‐two hybrid and Bimolecular fluorescence complementation (BiFC), we studied complex formation between BES1 and HSP90 under control conditions and active BR signalling. Further, we determined the effect of the pharmacological inhibition of HSP90 ATPase activity on hypocotyl elongation of bes1-D mutant. We determined that HSP90 interact with BES1 in the nucleus and in the cytoplasm. During active BR signalling, nuclear complexes were absent while cytoplasmic HSP90/BES1 complexes were prominent. Our results showed that the hypocotyl length of bes1‐D mutants was highly reduced when HSP90 was challenged by the geldanamycin (GDA) inhibitor of the ATPase activity of HSP90. Active BR signalling could not rescue the GDA effect on the hypocotyl elongation of bes1-D . Our results reveal that the constitutively active BES1 in the bes1‐D mutant is hypersensitive to GDA. The interaction of HSP90 with BES1 argues that HSP90 facilitate the nuclear metastable conformation of BES1 to regulate BR‐dependent gene expression, and our data show that HSP90 assist in the compartmentalised cycle of BES1 during active BR signalling. Abstract : HSP90 interacts with BES1 in the nucleus and in the cytoplasm, and HSP90 assists the compartmentalized cycle of BES1 during active BR signaling.